The Influence of Flow and Type of Variation in The Welding Electrode SMAW Against Carbon Steel Mechanical Propertis - I Made Gatot Karohika (Department of Mechanical Engineering, University of Udayana, 2009)
Welding is a joining process of 2 or more metal that is widely used in industry. To obtain good welding result it is needed appropriate filler and weld parameters to avoid weld defect and wide deference of mechanic properties between welded metal and base metal.In this experiment we used different filler and current (E 6010, 7018 ? 2,5mm ? 350mm , 100 dan 130 A)and use material carbon steel AISI 1045 and SMAW welding method. Rockwell C Hardness tested in welded metal, HAZ, and base metal area.The hardness number in welded metal and HAZ is reported higher than base metal area, the hardness number of welded metal and HAZ that use current 130 is higher than that one than use current 100 A,and hardness number in base metal relatifely similar. The hardness number of welded metal that use electrode 7018 is higher than hardness number of welded metal that use electrode 6010, and hardness number of HAZ and base metal is not affected significantly by the types of electrode.